Effects of Poverty on Education in Rural Pakistan - Abdul Hameed Phull; Nazar Hussain Phulpoto; Shoukat Ali Mahar; Saifullah Memon (Journal of Business and Social Review in Emerging Economies, 2022)
Purpose: The study's goal is to look into the impact of poverty on schooling in rural Pakistan. The purpose of the research is to see if pupils in Pakistan are truly affected by the country's economic situation and how much a standard of life can influence a student's education rural community.